Complete reaction mechanisms of mercury oxidation on halogenated activated carbon - Rungnim C. (2017)
© 2016 Elsevier B.V. The reaction mechanisms of mercury (Hg) adsorption and oxidation on halogenated activated carbon (AC) have been completely studied for the first time using density functional theory (DFT) method. Two different halogenated AC models, namely X-AC and X-AC-X (X = Cl, Br, I), were adopted. The results revealed that HgX is found to be stable-state on the AC edge since its further desorption from the AC as HgX, or further oxidation to HgX 2 , are energetically unfavorable. Remarkably, the halide type does not significantly affect the Hg adsorption energy but it strongly affects the activation energy barrier of HgX formation, which obviously increases in the order HgI < HgBr < HgCl. This trend coincides with the experimental observations which reported the efficiency of halogen impregnated AC for Hg elimination significantly decreases as I-AC > Br-AC > Cl-AC. Thus, the study of the complete reaction mechanism is essential because the adsorption energy can not be used as a guideline for the rational material design in the halide impregnated AC systems. The activation energy is an important descriptor for the predictions of sorbent reactivity to the Hg oxidation process.